A fiber-reinforced toughened biomedical alloy material and preparation method thereof

Modified nano-amorphous powder was prepared by high-speed ball milling, and combined with spinning technology and sintering treatment, fiber-reinforced toughening biomedical alloy materials were prepared, solving the problem of incompatibility of existing biomedical metal materials with human bone mechanics, and achieving the high strength, toughness, elastic modulus of the material close to human bones, wear resistance and biocompatibility.

CN116440321BActive Publication Date: 2025-04-22SHENZHEN PINGLE ORTHOPEDICS&TRAUMATOLOGY HOSPITAL
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211199047.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-29
Publication Date
2025-04-22
Estimated Expiration
2042-09-29

AI Technical Summary

Technical Problem

Existing biomedical metal materials such as stainless steel and titanium alloys have poor mechanical compatibility with human bones, resulting in bone loss, poor bone growth around the implant and inflammation.

Method used

Nano-amorphous powder is prepared by mixing Cu, Zr, Si, Ti and other elements with high-speed ball milling, and polyacrylamide is modified on its surface, combined with glycidol modified silk fibre protein and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) and other materials to prepare a spinning liquid for electrospinning to form a staple fiber. Then, the modified nano-amorphous powder is cold pressed, vacuum sintered and pressurized to prepare a fiber-reinforced toughened biomedical alloy material.

Benefits of technology

The material has high strength and toughness, its elastic modulus is close to that of the human skeleton, and its wear resistance and biocompatibility are good, solving the problem of incompatibility of existing materials with the human skeleton mechanics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003871488280000191
    Figure BDA0003871488280000191
Patent Text Reader

Abstract

The invention provides a fiber-reinforced toughened biomedical alloy material and a preparation method thereof. Firstly, nano-amorphous powder is obtained by mixing Cu, Zr, Si and Ti through high-speed ball milling, and the powder is modified by polyacrylamide to obtain modified nano-amorphous powder. Then, glycidol-modified silk fibroin, polyacrylamide-modified poly (3-hydroxybutyrate-co-3-hydroxyvalerate), trifluoroethyl methacrylate, a fluorine-containing photoinitiator and deionized water are prepared into a spinning solution, and electrostatic spinning is performed to obtain short fibers. Finally, the modified nano-amorphous powder and the short fibers are subjected to cold pressing, vacuum sintering and pressure densification treatment to obtain a biomedical alloy material. The biomedical alloy material has high strength and toughness, an elastic modulus similar to that of human bones, and good wear resistance and biocompatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field, and in particular to a fiber-reinforced and toughened biomedical alloy material and a preparation method thereof. Background Art

[0002] At present, biomedical materials used in clinical applications, such as bone implants and heart stents, are mostly made of stainless steel and titanium alloys. Stainless steel and titanium alloys have good biocompatibility, corrosion resistance and mechanical properties. Therefore, stainless steel and titanium alloys are widely used and recognized in the clinical medical community. However, existing metal bone implant materials such as stainless steel and titanium alloys have poor mechanical compatibility with human bones. The tensile strength of materials such as stainless steel and titanium alloys is more than 5.3 times higher than that of human bones, and the elastic modulus is more than 11 times higher. Bone implants such as stainless steel and titanium alloys have a great "stress shielding" effect on local bone tissue in the human body, which can induce shielding bone loss. This leads to the fragility of the original biological bone around the human bone implant, poor growth of new bone around the human bone implant, and inflammation caused by stress concentration between the human bone implant and the biological bone. At the same time, the surgical removal of human bone implants increases the pain, time and cost of medical personnel.

[0003] Bulk amorphous alloys are new materials that have emerged in recent years. Due to the long-range disorder of atomic arrangement in amorphous alloys, there are no defects such as grain boundaries and dislocations. Compared with the corresponding crystalline alloys, amorphous alloys have extremely high strength, low elastic modulus, good corrosion resistance and wear resistance. In recent years, titanium-based amorphous alloys have become one of the hot spots in the field of amorphous alloy research due to their superior performance and potential application value, but the alloy system of titanium-based amorphous alloys currently prepared has great limitations. However, the room temperature deformation mechanism of amorphous alloys is adiabatic shear deformation, and the room temperature deformation is highly localized, resulting in almost no plasticity of amorphous alloys at room temperature; powder metallurgy is an effective way to prepare larger-sized bulk amorphous alloys, but it is difficult to sinter amorphous alloy powders into dense bulk amorphous. Too high a temperature will cause the amorphous alloy powder to crystallize, while too low a temperature will make the alloy difficult to sinter.

[0004] Patent CN106119742B discloses a titanium oxide-titanium nitride whisker toughened magnesium alloy biomedical material, which forms directionally arranged titanium oxide-titanium carbide whiskers and magnesium alloy matrix material along the extrusion streamline. Its elastic modulus is still far behind that of human bones, and its wear resistance is also poor. Summary of the invention

[0005] The purpose of the present invention is to provide a fiber-reinforced toughened biomedical alloy material and a preparation method thereof, which has high strength and toughness, an elastic modulus similar to that of human bones, and good wear resistance and biocompatibility.

[0006] To achieve the above object, the present invention is implemented by the following scheme:

[0007] A method for preparing a fiber-reinforced toughened biomedical alloy material, the specific steps are as follows:

[0008] (1) firstly, Cu, Zr, Si and Ti with a purity of 99.9999% are mixed in a molar ratio of 100:8-10:20-30:20-30 and subjected to high-speed ball milling to obtain nano-amorphous powder, and then polyacrylamide is modified on the surface of the nano-amorphous powder to obtain modified nano-amorphous powder;

[0009] (2) preparing a spinning solution by mixing glycidyl-modified silk fibroin with polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate), trifluoroethyl methacrylate, a fluorine-containing photoinitiator and deionized water under light-proof conditions, electrospinning the solution under ultraviolet light to obtain fibers, and cutting the fibers into short fibers of 1 to 2 mm;

[0010] (3) Finally, the modified nano-amorphous powder and the short fibers are subjected to cold pressing, vacuum sintering and pressure densification according to a mass ratio of 1:0.1-0.2 to obtain the biomedical alloy material.

[0011] Preferably, in step (1), the process conditions of high-speed ball milling are as follows: the mass ratio of the grinding balls is 1:2, the diameters of the grinding balls are 8 mm and 5 mm respectively, the ball-to-material ratio is 1.05:1, argon protection is used during the ball milling process, the ball milling speed is 300 r / min, and the grinding time is 12 to 15 hours. The preparation work before ball milling should be carried out in a vacuum glove box.

[0012] Further preferably, 0.2-0.4% of the weight of stearic acid based on the raw material is added as a lubricant during ball milling to prevent the raw material from adhering to the bottom or inner wall of the ball mill.

[0013] Preferably, in step (1), the preparation method of the modified nano-amorphous powder is as follows, based on parts by weight: first, 1 part of nano-amorphous powder and 0.002-0.003 parts of initiator are added to 5-8 parts of 20-30% mass concentration of acrylamide aqueous solution, and ultrasonically oscillated at 400-500W for 30-40 minutes to obtain a premixed solution; then, ultraviolet light is irradiated to initiate a polymerization reaction of acrylamide to obtain the modified nano-amorphous powder.

[0014] Further preferably, the initiator is benzophenone, tetraethyl Michler's ketone or 4-isopropylthioxanthone; and the ultraviolet light irradiation time is 2 to 3 hours.

[0015] Preferably, in step (2), the spinning solution is prepared as follows, in parts by weight: first, 1 to 2 parts of glycidyl-modified silk fibroin and 0.1 to 0.2 parts of polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) are added to 100 parts of deionized water, and stirred until completely dissolved. Then, 0.05 to 0.08 parts of trifluoroethyl methacrylate and 0.02 to 0.03 parts of a fluorine-containing photoinitiator are added under light-proof conditions, and stirred until completely dissolved to obtain the spinning solution.

[0016] Preferably, in step (2), the fluorine-containing photoinitiator is prepared using perfluoroalkyl ethyl acrylate and isophorone diisocyanate as raw materials, with specific reference to the document “Preparation and Performance Study of a Fluorine-Containing Photoinitiator” (Liang Shuang et al., Journal of Hebei University of Technology, 2017, 46(6), 65-70).

[0017] Preferably, in step (2), the process conditions of electrospinning are: spinning voltage 10-20 kV, the distance from the spinning nozzle to the receiver is 20-25 cm, the spinning nozzle diameter is 1.0 mm, and the flow rate is controlled to 1.5-2 mL / h.

[0018] Preferably, in step (2), the glycidol-modified silk fibroin is prepared by the following method, based on parts by weight: first, 1 part of silk fibroin, 0.2-0.3 parts of glycidol and 0.1-0.2 parts of sodium chloride are added to 10-12 parts of deionized water, stirred until completely dissolved, stirred and reacted at 60-70° C. for 2-3 hours, naturally cooled to room temperature (25° C.), and rinsed with deionized water for 2-4 days to remove unreacted substances, thereby obtaining the glycidol-modified silk fibroin.

[0019] Preferably, in step (2), the polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) is prepared by the following method, based on parts by weight: first, 1 part of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) and 0.002-0.003 parts of initiator are added to 5-8 parts of 20-30% acrylamide aqueous solution, and ultrasonically oscillated at 400-500W for 30-40 minutes to obtain a premixed solution; and then ultraviolet light is irradiated to initiate a polymerization reaction of acrylamide to obtain the product.

[0020] Further preferably, the initiator is benzophenone, tetraethyl Michler's ketone or 4-isopropylthioxanthone; and the ultraviolet light irradiation time is 2 to 3 hours.

[0021] Preferably, the specific method of step (3) is as follows: the modified nano-amorphous powder and the short fibers are uniformly mixed and then transferred to a high-strength graphite mold for cold compaction, and then transferred to a vacuum hot pressing furnace for heating and degassing, vacuum sintering at 150-180°C and 60-90MPa for 50-80 minutes, naturally cooling to 80-90°C, and pressurizing and densifying at 50-60MPa for 4-6 hours to obtain the biomedical alloy material.

[0022] A fiber-reinforced and toughened biomedical alloy material is obtained by the preparation method.

[0023] The beneficial effects of the present invention are:

[0024] The invention firstly obtains nano amorphous powder by mixing Cu, Zr, Si and Ti through high-speed ball milling, and performs polyacrylamide modification on the powder to obtain modified nano amorphous powder. Then, glycidol-modified silk fibroin, polyacrylamide-modified poly (3-hydroxybutyrate-co-3-hydroxyvalerate), trifluoroethyl methacrylate, fluorine-containing photoinitiator and deionized water are prepared into spinning solution and electrostatic spinning is performed to obtain short fibers. Finally, the modified nano amorphous powder and the short fibers are subjected to cold pressing, vacuum sintering and pressure densification treatment to obtain a biomedical alloy material with high strength and toughness, elastic modulus similar to that of human bones, and good wear resistance and biocompatibility.

[0025] Among them, the nano-amorphous powder prepared by high-speed ball milling of a mixture of Cu, Zr, Si and Ti in a specific ratio has high strength, low elastic modulus and good wear resistance. The raw materials have no cytotoxicity and neurotoxicity to the human body and are safe. Since the nano-amorphous powder has poor plasticity and is difficult to sinter, the present invention forms a polyacrylamide coating layer on its surface and introduces amide groups, which can form hydrogen bonds with short fibers to enhance toughness. The amide groups improve hydrophilicity, thereby improving biocompatibility.

[0026] Silk fibroin is modified with glycidol to form a gel form, which enhances toughness. However, the gel is thermally irreversible, and heating during subsequent processing will cause volume shrinkage. Therefore, the applicant added polyacrylamide-modified poly (3-hydroxybutyrate-co-3-hydroxyvalerate) and trifluoroethyl methacrylate to polymerize and fill the pores between the gel to play a supporting role, avoid volume shrinkage, and further enhance toughness.

[0027] The addition of poly (3-hydroxybutyrate-co-3-hydroxyvalerate) helps to improve the mechanical properties of the product, but it has a high degree of crystallinity and poor hydrophilicity, and its biocompatibility is naturally poor. Therefore, the present invention forms polyacrylamide modification on its surface and introduces amide groups, which greatly improves its hydrophilicity and significantly improves its biocompatibility. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] A method for preparing a fiber-reinforced toughened biomedical alloy material, the specific steps are as follows:

[0031] (1) firstly, Cu, Zr, Si, and Ti with a purity of 99.9999% are mixed in a molar ratio of 100:8:30:20 and subjected to high-speed ball milling to obtain nano-amorphous powder, and then the surface of the nano-amorphous powder is modified with polyacrylamide to obtain modified nano-amorphous powder;

[0032] (2) then preparing a spinning solution with glycidyl-modified silk fibroin, polyacrylamide-modified poly (3-hydroxybutyrate-co-3-hydroxyvalerate), trifluoroethyl methacrylate, a fluorine-containing photoinitiator and deionized water under light-proof conditions, electrospinning the solution under ultraviolet light to obtain fibers, and cutting the fibers into 2 mm short fibers;

[0033] (3) Finally, the modified nano-amorphous powder and the short fibers are subjected to cold pressing, vacuum sintering and pressure densification in a mass ratio of 1:0.1 to obtain the biomedical alloy material.

[0034] In step (1), the process conditions of high-speed ball milling are as follows: the mass ratio of the grinding balls is 1:2, the diameters of the grinding balls are 8 mm and 5 mm respectively, the ball-to-material ratio is 1.05:1, argon protection is used during the ball milling process, the ball milling speed is 300 r / min, and the grinding time is 15 hours. The preparation work before ball milling should be carried out in a vacuum glove box.

[0035] During ball milling, 0.2% of the raw material weight of stearic acid was added as a lubricant to prevent the raw material from sticking to the bottom or inner wall of the ball mill.

[0036] In step (1), the preparation method of the modified nano-amorphous powder is as follows: first, 1 kg of nano-amorphous powder and 0.003 kg of initiator are added to 5 kg of 30% acrylamide aqueous solution, and ultrasonically oscillated at 400W for 40 minutes to obtain a premixed solution; then, ultraviolet light is irradiated to initiate acrylamide polymerization reaction to obtain the modified nano-amorphous powder.

[0037] The initiator is benzophenone; the ultraviolet light irradiation time is 2 hours.

[0038] In step (2), the spinning solution is prepared as follows: first, 2 kg of glycidyl-modified silk fibroin and 0.1 kg of polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) are added to 100 kg of deionized water, and stirred until completely dissolved. Then, 0.08 kg of trifluoroethyl methacrylate and 0.02 kg of fluorine-containing photoinitiator are added under light-proof conditions, and stirred until completely dissolved to obtain the spinning solution.

[0039] In step (2), the fluorine-containing photoinitiator is prepared using perfluoroalkyl ethyl acrylate and isophorone diisocyanate as raw materials, with specific reference to the document “Preparation and Performance Study of a Fluorine-Containing Photoinitiator” (Liang Shuang et al., Journal of Hebei University of Technology, 2017, 46(6), 65-70).

[0040] In step (2), the process conditions of electrospinning are: spinning voltage 20 kV, the distance from the spinning nozzle to the receiver is 20 cm, the spinning nozzle diameter is 1.0 mm, and the flow rate is controlled at 2 mL / h.

[0041] In step (2), the glycidol-modified silk fibroin is prepared by the following method: first, 1 kg of silk fibroin, 0.2 kg of glycidol and 0.2 kg of sodium chloride are added to 10 kg of deionized water, stirred until completely dissolved, stirred and reacted at 70° C. for 2 hours, naturally cooled to room temperature (25° C.), and rinsed with deionized water for 4 days to remove unreacted substances, thereby obtaining the glycidol-modified silk fibroin.

[0042] In step (2), polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) is prepared by the following method: first, 1 kg of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) and 0.002 kg of initiator are added to 8 kg of 20% acrylamide aqueous solution, and ultrasonically oscillated at 500 W for 30 minutes to obtain a premixed solution; and then ultraviolet light is irradiated to initiate a polymerization reaction of acrylamide to obtain the obtained solution.

[0043] The initiator is benzophenone; the ultraviolet light irradiation time is 3 hours.

[0044] The specific method of step (3) is as follows: the modified nano-amorphous powder and the short fibers are uniformly mixed and then transferred to a high-strength graphite mold for cold compaction, and then transferred to a vacuum hot pressing furnace for heating and degassing, vacuum sintering at 150°C and 90MPa for 50 minutes, naturally cooling to 90°C, and pressurizing and densifying at 50MPa for 6 hours to obtain the biomedical alloy material.

[0045] Example 2

[0046] A method for preparing a fiber-reinforced toughened biomedical alloy material, the specific steps are as follows:

[0047] (1) firstly, Cu, Zr, Si and Ti with a purity of 99.9999% are mixed in a molar ratio of 100:10:20:30 and subjected to high-speed ball milling to obtain nano-amorphous powder, and then the surface of the nano-amorphous powder is modified with polyacrylamide to obtain modified nano-amorphous powder;

[0048] (2) then preparing a spinning solution with glycidyl-modified silk fibroin, polyacrylamide-modified poly (3-hydroxybutyrate-co-3-hydroxyvalerate), trifluoroethyl methacrylate, a fluorine-containing photoinitiator and deionized water under light-proof conditions, electrospinning the solution under ultraviolet light to obtain fibers, and cutting the fibers into 1 mm short fibers;

[0049] (3) Finally, the modified nano-amorphous powder and the short fibers are subjected to cold pressing, vacuum sintering and pressure densification in a mass ratio of 1:0.2 to obtain the biomedical alloy material.

[0050] In step (1), the process conditions of high-speed ball milling are as follows: the mass ratio of the grinding balls is 1:2, the diameters of the grinding balls are 8 mm and 5 mm respectively, the ball-to-material ratio is 1.05:1, argon protection is used during the ball milling process, the ball milling speed is 300 r / min, and the grinding time is 12 hours. The preparation work before ball milling should be carried out in a vacuum glove box.

[0051] During ball milling, 0.4% of the raw material weight of stearic acid was added as a lubricant to prevent the raw material from sticking to the bottom or inner wall of the ball mill.

[0052] In step (1), the preparation method of the modified nano-amorphous powder is as follows: first, 1 kg of nano-amorphous powder and 0.002 kg of initiator are added to 8 kg of 20% acrylamide aqueous solution, and ultrasonically oscillated at 500 W for 30 minutes to obtain a premixed solution; then, ultraviolet light is irradiated to initiate acrylamide polymerization reaction to obtain the modified nano-amorphous powder.

[0053] The initiator is tetraethyl Michler's ketone; the ultraviolet light irradiation time is 3 hours.

[0054] In step (2), the spinning solution is prepared as follows: first, 1 kg of glycidyl-modified silk fibroin and 0.2 kg of polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) are added to 100 kg of deionized water, and stirred until completely dissolved. Then, 0.05 kg of trifluoroethyl methacrylate and 0.03 kg of fluorine-containing photoinitiator are added under light-proof conditions, and stirred until completely dissolved to obtain the spinning solution.

[0055] In step (2), the fluorine-containing photoinitiator is prepared using perfluoroalkyl ethyl acrylate and isophorone diisocyanate as raw materials, with specific reference to the document “Preparation and Performance Study of a Fluorine-Containing Photoinitiator” (Liang Shuang et al., Journal of Hebei University of Technology, 2017, 46(6), 65-70).

[0056] In step (2), the process conditions of electrospinning are: spinning voltage 10 kV, the distance from the spinning nozzle to the receiver is 25 cm, the spinning nozzle diameter is 1.0 mm, and the flow rate is controlled at 1.5 mL / h.

[0057] In step (2), the glycidol-modified silk fibroin is prepared by the following method: first, 1 kg of silk fibroin, 0.3 kg of glycidol and 0.1 kg of sodium chloride are added to 12 kg of deionized water, stirred until completely dissolved, stirred and reacted at 60° C. for 3 hours, naturally cooled to room temperature (25° C.), and immersed in deionized water for 2 days to remove unreacted substances, thereby obtaining the glycidol-modified silk fibroin.

[0058] In step (2), polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) is prepared by the following method: first, 1 kg of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) and 0.003 kg of initiator are added to 5 kg of 30% acrylamide aqueous solution, and ultrasonically oscillated at 400 W for 40 minutes to obtain a premixed solution; and then ultraviolet light is irradiated to initiate a polymerization reaction of acrylamide to obtain the obtained solution.

[0059] The initiator is tetraethyl Michler's ketone; the ultraviolet light irradiation time is 2 hours.

[0060] The specific method of step (3) is as follows: the modified nano-amorphous powder and the short fibers are uniformly mixed and then transferred to a high-strength graphite mold for cold compaction, and then transferred to a vacuum hot pressing furnace for heating and degassing, vacuum sintering at 180°C and 60MPa for 80 minutes, naturally cooling to 80°C, and pressurizing and densifying at 60MPa for 4 hours to obtain the biomedical alloy material.

[0061] Example 3

[0062] A method for preparing a fiber-reinforced toughened biomedical alloy material, the specific steps are as follows:

[0063] (1) firstly, Cu, Zr, Si, and Ti with a purity of 99.9999% are mixed in a molar ratio of 100:9:25:25 and subjected to high-speed ball milling to obtain nano-amorphous powder, and then the surface of the nano-amorphous powder is modified with polyacrylamide to obtain modified nano-amorphous powder;

[0064] (2) then preparing a spinning solution with glycidyl-modified silk fibroin, polyacrylamide-modified poly (3-hydroxybutyrate-co-3-hydroxyvalerate), trifluoroethyl methacrylate, a fluorine-containing photoinitiator and deionized water under light-proof conditions, electrospinning the solution under ultraviolet light to obtain fibers, and cutting the fibers into 1.5 mm short fibers;

[0065] (3) Finally, the modified nano-amorphous powder and the short fibers are subjected to cold pressing, vacuum sintering and pressure densification in a mass ratio of 1:0.15 to obtain the biomedical alloy material.

[0066] In step (1), the process conditions of high-speed ball milling are as follows: the mass ratio of the grinding balls is 1:2, the diameters of the grinding balls are 8 mm and 5 mm respectively, the ball-to-material ratio is 1.05:1, argon protection is used during the ball milling process, the ball milling speed is 300 r / min, and the grinding time is 14 hours. The preparation work before ball milling should be carried out in a vacuum glove box.

[0067] During ball milling, 0.3% of the raw material weight of stearic acid was added as a lubricant to prevent the raw material from sticking to the bottom or inner wall of the ball mill.

[0068] In step (1), the preparation method of the modified nano-amorphous powder is as follows: first, 1 kg of nano-amorphous powder and 0.0025 kg of initiator are added to 6 kg of 25% mass concentration acrylamide aqueous solution, and ultrasonically oscillated at 450W for 35 minutes to obtain a premixed solution; then, ultraviolet light is irradiated to initiate acrylamide polymerization reaction to obtain the modified nano-amorphous powder.

[0069] The initiator is 4-isopropylthioxanthone; and the ultraviolet light irradiation time is 2.5 hours.

[0070] In step (2), the spinning solution is prepared as follows: first, 1.5 kg of glycidyl-modified silk fibroin and 0.15 kg of polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) are added to 100 kg of deionized water, and stirred until completely dissolved. Then, 0.07 kg of trifluoroethyl methacrylate and 0.025 kg of fluorine-containing photoinitiator are added under light-proof conditions, and stirred until completely dissolved to obtain the spinning solution.

[0071] In step (2), the fluorine-containing photoinitiator is prepared using perfluoroalkyl ethyl acrylate and isophorone diisocyanate as raw materials, with specific reference to the document “Preparation and Performance Study of a Fluorine-Containing Photoinitiator” (Liang Shuang et al., Journal of Hebei University of Technology, 2017, 46(6), 65-70).

[0072] In step (2), the process conditions of electrospinning are: spinning voltage 15 kV, the distance from the spinning nozzle to the receiver is 22 cm, the spinning nozzle diameter is 1.0 mm, and the flow rate is controlled at 1.8 mL / h.

[0073] In step (2), the glycidol-modified silk fibroin is prepared by the following method: first, 1 kg of silk fibroin, 0.25 kg of glycidol and 0.15 kg of sodium chloride are added to 11 kg of deionized water, stirred until completely dissolved, stirred and reacted at 65° C. for 2.5 hours, naturally cooled to room temperature (25° C.), and rinsed with deionized water for 3 days to remove unreacted substances, thereby obtaining the glycidol-modified silk fibroin.

[0074] In step (2), polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) is prepared by the following method: first, 1 kg of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) and 0.0025 kg of initiator are added to 6 kg of 25% mass concentration acrylamide aqueous solution, and ultrasonically oscillated at 450 W for 35 minutes to obtain a premixed solution; and then ultraviolet light is irradiated to initiate a polymerization reaction of acrylamide to obtain the obtained product.

[0075] The initiator is 4-isopropylthioxanthone; and the ultraviolet light irradiation time is 2.5 hours.

[0076] The specific method of step (3) is as follows: the modified nano-amorphous powder and the short fibers are uniformly mixed and then transferred to a high-strength graphite mold for cold compaction, and then transferred to a vacuum hot pressing furnace for heating and degassing, vacuum sintering at 165°C and 80MPa for 70 minutes, naturally cooling to 85°C, and pressurizing and densifying at 55MPa for 5 hours to obtain the biomedical alloy material.

[0077] Comparative Example 1

[0078] A method for preparing a biomedical alloy material, the specific steps are as follows:

[0079] (1) firstly, Ta, Zr, Si, and Ti with a purity of 99.9999% are mixed in a molar ratio of 100:8:30:20 and subjected to high-speed ball milling to obtain nano-amorphous powder, and then the surface of the nano-amorphous powder is modified with polyacrylamide to obtain modified nano-amorphous powder;

[0080] (2) then preparing a spinning solution with glycidyl-modified silk fibroin, polyacrylamide-modified poly (3-hydroxybutyrate-co-3-hydroxyvalerate), trifluoroethyl methacrylate, a fluorine-containing photoinitiator and deionized water under light-proof conditions, electrospinning the solution under ultraviolet light to obtain fibers, and cutting the fibers into 2 mm short fibers;

[0081] (3) Finally, the modified nano-amorphous powder and the short fibers are subjected to cold pressing, vacuum sintering and pressure densification in a mass ratio of 1:0.1 to obtain the biomedical alloy material.

[0082] In step (1), the process conditions of high-speed ball milling are as follows: the mass ratio of the grinding balls is 1:2, the diameters of the grinding balls are 8 mm and 5 mm respectively, the ball-to-material ratio is 1.05:1, argon protection is used during the ball milling process, the ball milling speed is 300 r / min, and the grinding time is 15 hours. The preparation work before ball milling should be carried out in a vacuum glove box.

[0083] During ball milling, 0.2% of the raw material weight of stearic acid was added as a lubricant to prevent the raw material from sticking to the bottom or inner wall of the ball mill.

[0084] In step (1), the preparation method of the modified nano-amorphous powder is as follows: first, 1 kg of nano-amorphous powder and 0.003 kg of initiator are added to 5 kg of 30% acrylamide aqueous solution, and ultrasonically oscillated at 400W for 40 minutes to obtain a premixed solution; then, ultraviolet light is irradiated to initiate acrylamide polymerization reaction to obtain the modified nano-amorphous powder.

[0085] The initiator is benzophenone; the ultraviolet light irradiation time is 2 hours.

[0086] In step (2), the spinning solution is prepared as follows: first, 2 kg of glycidyl-modified silk fibroin and 0.1 kg of polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) are added to 100 kg of deionized water, and stirred until completely dissolved. Then, 0.08 kg of trifluoroethyl methacrylate and 0.02 kg of fluorine-containing photoinitiator are added under light-proof conditions, and stirred until completely dissolved to obtain the spinning solution.

[0087] In step (2), the fluorine-containing photoinitiator is prepared using perfluoroalkyl ethyl acrylate and isophorone diisocyanate as raw materials, with specific reference to the document “Preparation and Performance Study of a Fluorine-Containing Photoinitiator” (Liang Shuang et al., Journal of Hebei University of Technology, 2017, 46(6), 65-70).

[0088] In step (2), the process conditions of electrospinning are: spinning voltage 20 kV, the distance from the spinning nozzle to the receiver is 20 cm, the spinning nozzle diameter is 1.0 mm, and the flow rate is controlled at 2 mL / h.

[0089] In step (2), the glycidol-modified silk fibroin is prepared by the following method: first, 1 kg of silk fibroin, 0.2 kg of glycidol and 0.2 kg of sodium chloride are added to 10 kg of deionized water, stirred until completely dissolved, stirred and reacted at 70° C. for 2 hours, naturally cooled to room temperature (25° C.), and rinsed with deionized water for 4 days to remove unreacted substances, thereby obtaining the glycidol-modified silk fibroin.

[0090] In step (2), polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) is prepared by the following method: first, 1 kg of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) and 0.002 kg of initiator are added to 8 kg of 20% acrylamide aqueous solution, and ultrasonically oscillated at 500 W for 30 minutes to obtain a premixed solution; and then ultraviolet light is irradiated to initiate a polymerization reaction of acrylamide to obtain the obtained solution.

[0091] The initiator is benzophenone; the ultraviolet light irradiation time is 3 hours.

[0092] The specific method of step (3) is as follows: the modified nano-amorphous powder and the short fibers are uniformly mixed and then transferred to a high-strength graphite mold for cold compaction, and then transferred to a vacuum hot pressing furnace for heating and degassing, vacuum sintering at 150°C and 90MPa for 50 minutes, naturally cooling to 90°C, and pressurizing and densifying at 50MPa for 6 hours to obtain the biomedical alloy material.

[0093] Comparative Example 2

[0094] A method for preparing a biomedical alloy material, the specific steps are as follows:

[0095] (1) firstly, Cu, Zr, Si and Ti with a purity of 99.9999% were mixed in a molar ratio of 100:8:30:20 and subjected to high-speed ball milling to obtain nano-amorphous powder;

[0096] (2) then preparing a spinning solution with glycidyl-modified silk fibroin, polyacrylamide-modified poly (3-hydroxybutyrate-co-3-hydroxyvalerate), trifluoroethyl methacrylate, a fluorine-containing photoinitiator and deionized water under light-proof conditions, electrospinning the solution under ultraviolet light to obtain fibers, and cutting the fibers into 2 mm short fibers;

[0097] (3) Finally, the nano-amorphous powder and the short fibers are cold pressed, vacuum sintered and pressurized to obtain the biomedical alloy material according to a mass ratio of 1:0.1.

[0098] In step (1), the process conditions of high-speed ball milling are as follows: the mass ratio of the grinding balls is 1:2, the diameters of the grinding balls are 8 mm and 5 mm respectively, the ball-to-material ratio is 1.05:1, argon protection is used during the ball milling process, the ball milling speed is 300 r / min, and the grinding time is 15 hours. The preparation work before ball milling should be carried out in a vacuum glove box.

[0099] During ball milling, 0.2% of the raw material weight of stearic acid was added as a lubricant to prevent the raw material from sticking to the bottom or inner wall of the ball mill.

[0100] In step (2), the spinning solution is prepared as follows: first, 2 kg of glycidyl-modified silk fibroin and 0.1 kg of polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) are added to 100 kg of deionized water, and stirred until completely dissolved. Then, 0.08 kg of trifluoroethyl methacrylate and 0.02 kg of fluorine-containing photoinitiator are added under light-proof conditions, and stirred until completely dissolved to obtain the spinning solution.

[0101] In step (2), the fluorine-containing photoinitiator is prepared using perfluoroalkyl ethyl acrylate and isophorone diisocyanate as raw materials, with specific reference to the document “Preparation and Performance Study of a Fluorine-Containing Photoinitiator” (Liang Shuang et al., Journal of Hebei University of Technology, 2017, 46(6), 65-70).

[0102] In step (2), the process conditions of electrospinning are: spinning voltage 20 kV, the distance from the spinning nozzle to the receiver is 20 cm, the spinning nozzle diameter is 1.0 mm, and the flow rate is controlled at 2 mL / h.

[0103] In step (2), the glycidol-modified silk fibroin is prepared by the following method: first, 1 kg of silk fibroin, 0.2 kg of glycidol and 0.2 kg of sodium chloride are added to 10 kg of deionized water, stirred until completely dissolved, stirred and reacted at 70° C. for 2 hours, naturally cooled to room temperature (25° C.), and rinsed with deionized water for 4 days to remove unreacted substances, thereby obtaining the glycidol-modified silk fibroin.

[0104] In step (2), polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) is prepared by the following method: first, 1 kg of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) and 0.002 kg of initiator are added to 8 kg of 20% acrylamide aqueous solution, and ultrasonically oscillated at 500 W for 30 minutes to obtain a premixed solution; and then ultraviolet light is irradiated to initiate a polymerization reaction of acrylamide to obtain the obtained solution.

[0105] The initiator is benzophenone; the ultraviolet light irradiation time is 3 hours.

[0106] The specific method of step (3) is as follows: the nano-amorphous powder and the short fibers are uniformly mixed and then transferred to a high-strength graphite mold for cold compaction, and then transferred to a vacuum hot pressing furnace for heating and degassing, vacuum sintering at 150°C and 90MPa for 50 minutes, naturally cooling to 90°C, and pressurizing and densifying at 50MPa for 6 hours to obtain the biomedical alloy material.

[0107] Comparative Example 3

[0108] A method for preparing a biomedical alloy material, the specific steps are as follows:

[0109] (1) firstly, Cu, Zr, Si, and Ti with a purity of 99.9999% are mixed in a molar ratio of 100:8:30:20 and subjected to high-speed ball milling to obtain nano-amorphous powder, and then the surface of the nano-amorphous powder is modified with polyacrylamide to obtain modified nano-amorphous powder;

[0110] (2) preparing a spinning solution with silk fibroin, trifluoroethyl methacrylate, a fluorine-containing photoinitiator and deionized water under light-proof conditions, electrospinning the solution under ultraviolet light to obtain fibers, and cutting the fibers into 2 mm short fibers;

[0111] (3) Finally, the modified nano-amorphous powder and the short fibers are subjected to cold pressing, vacuum sintering and pressure densification in a mass ratio of 1:0.1 to obtain the biomedical alloy material.

[0112] In step (1), the process conditions of high-speed ball milling are as follows: the mass ratio of the grinding balls is 1:2, the diameters of the grinding balls are 8 mm and 5 mm respectively, the ball-to-material ratio is 1.05:1, argon protection is used during the ball milling process, the ball milling speed is 300 r / min, and the grinding time is 15 hours. The preparation work before ball milling should be carried out in a vacuum glove box.

[0113] During ball milling, 0.2% of the raw material weight of stearic acid was added as a lubricant to prevent the raw material from sticking to the bottom or inner wall of the ball mill.

[0114] In step (1), the preparation method of the modified nano-amorphous powder is as follows: first, 1 kg of nano-amorphous powder and 0.003 kg of initiator are added to 5 kg of 30% acrylamide aqueous solution, and ultrasonically oscillated at 400W for 40 minutes to obtain a premixed solution; then, ultraviolet light is irradiated to initiate acrylamide polymerization reaction to obtain the modified nano-amorphous powder.

[0115] The initiator is benzophenone; the ultraviolet light irradiation time is 2 hours.

[0116] In step (2), the spinning solution is prepared as follows: first, 2 kg of silk fibroin is added to 100 kg of deionized water, and stirred until completely dissolved. Then, 0.08 kg of trifluoroethyl methacrylate and 0.02 kg of fluorine-containing photoinitiator are added under light-proof conditions, and stirred until completely dissolved to obtain the spinning solution.

[0117] In step (2), the fluorine-containing photoinitiator is prepared using perfluoroalkyl ethyl acrylate and isophorone diisocyanate as raw materials, with specific reference to the document “Preparation and Performance Study of a Fluorine-Containing Photoinitiator” (Liang Shuang et al., Journal of Hebei University of Technology, 2017, 46(6), 65-70).

[0118] In step (2), the process conditions of electrospinning are: spinning voltage 20 kV, the distance from the spinning nozzle to the receiver is 20 cm, the spinning nozzle diameter is 1.0 mm, and the flow rate is controlled at 2 mL / h.

[0119] The specific method of step (3) is as follows: the modified nano-amorphous powder and the short fibers are uniformly mixed and then transferred to a high-strength graphite mold for cold compaction, and then transferred to a vacuum hot pressing furnace for heating and degassing, vacuum sintering at 150°C and 90MPa for 50 minutes, naturally cooling to 90°C, and pressurizing and densifying at 50MPa for 6 hours to obtain the biomedical alloy material.

[0120] Comparative Example 4

[0121] A method for preparing a biomedical alloy material, the specific steps are as follows:

[0122] (1) firstly, Cu, Zr, Si, and Ti with a purity of 99.9999% are mixed in a molar ratio of 100:8:30:20 and subjected to high-speed ball milling to obtain nano-amorphous powder, and then the surface of the nano-amorphous powder is modified with polyacrylamide to obtain modified nano-amorphous powder;

[0123] (2) preparing a mixed solution of glycidyl-modified silk fibroin, polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate), trifluoroethyl methacrylate, a fluorine-containing photoinitiator and deionized water under light-proof conditions, polymerizing under ultraviolet light, and crushing the obtained polymer into particles with a diameter of 2 mm;

[0124] (3) Finally, the modified nano-amorphous powder and the short fibers are subjected to cold pressing, vacuum sintering and pressure densification in a mass ratio of 1:0.1 to obtain the biomedical alloy material.

[0125] In step (1), the process conditions of high-speed ball milling are as follows: the mass ratio of the grinding balls is 1:2, the diameters of the grinding balls are 8 mm and 5 mm respectively, the ball-to-material ratio is 1.05:1, argon protection is used during the ball milling process, the ball milling speed is 300 r / min, and the grinding time is 15 hours. The preparation work before ball milling should be carried out in a vacuum glove box.

[0126] During ball milling, 0.2% of the raw material weight of stearic acid was added as a lubricant to prevent the raw material from sticking to the bottom or inner wall of the ball mill.

[0127] In step (1), the preparation method of the modified nano-amorphous powder is as follows: first, 1 kg of nano-amorphous powder and 0.003 kg of initiator are added to 5 kg of 30% acrylamide aqueous solution, and ultrasonically oscillated at 400W for 40 minutes to obtain a premixed solution; then, ultraviolet light is irradiated to initiate acrylamide polymerization reaction to obtain the modified nano-amorphous powder.

[0128] The initiator is benzophenone; the ultraviolet light irradiation time is 2 hours.

[0129] In step (2), the mixed solution is prepared as follows: first, 2 kg of glycidyl-modified silk fibroin and 0.1 kg of polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) are added to 100 kg of deionized water, and stirred until completely dissolved. Then, 0.08 kg of trifluoroethyl methacrylate and 0.02 kg of fluorine-containing photoinitiator are added under light-proof conditions, and stirred until completely dissolved to obtain the mixed solution.

[0130] In step (2), the fluorine-containing photoinitiator is prepared using perfluoroalkyl ethyl acrylate and isophorone diisocyanate as raw materials, with specific reference to the document “Preparation and Performance Study of a Fluorine-Containing Photoinitiator” (Liang Shuang et al., Journal of Hebei University of Technology, 2017, 46(6), 65-70).

[0131] In step (2), the glycidol-modified silk fibroin is prepared by the following method: first, 1 kg of silk fibroin, 0.2 kg of glycidol and 0.2 kg of sodium chloride are added to 10 kg of deionized water, stirred until completely dissolved, stirred and reacted at 70° C. for 2 hours, naturally cooled to room temperature (25° C.), and rinsed with deionized water for 4 days to remove unreacted substances, thereby obtaining the glycidol-modified silk fibroin.

[0132] In step (2), polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) is prepared by the following method: first, 1 kg of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) and 0.002 kg of initiator are added to 8 kg of 20% acrylamide aqueous solution, and ultrasonically oscillated at 500 W for 30 minutes to obtain a premixed solution; and then ultraviolet light is irradiated to initiate a polymerization reaction of acrylamide to obtain the obtained solution.

[0133] The initiator is benzophenone; the ultraviolet light irradiation time is 3 hours.

[0134] In step (2), the ultraviolet light irradiation polymerization time is 2 hours.

[0135] The specific method of step (3) is as follows: the modified nano-amorphous powder and the short fibers are uniformly mixed and then transferred to a high-strength graphite mold for cold compaction, and then transferred to a vacuum hot pressing furnace for heating and degassing, vacuum sintering at 150°C and 90MPa for 50 minutes, naturally cooling to 90°C, and pressurizing and densifying at 50MPa for 6 hours to obtain the biomedical alloy material.

[0136] Test example

[0137] 1. Biocompatibility study

[0138] The biocompatibility of the biomedical alloy materials obtained in Examples 1 to 3 and Comparative Examples 1 and 2 was investigated. The specific method is as follows: Cell Counting Kit 8 (CCK8), human bone marrow mesenchymal stem cells (HBMSC) were cultured to the third generation, the cells were plated in a 96-well plate, and the CCK8 test was performed after culturing in a cell incubator at 37.0°C and 5% CO2 partial pressure for 24 hours, and the relative proliferation rate of the cells was calculated by cell counting. The control group was a cell culture without biomedical alloy materials, and the results are shown in Table 1.

[0139] Table 1. Biocompatibility study

[0140] Relative cell proliferation rate (%) Example 1 137.8 Example 2 137.9 Example 3 138.1 Control group 103.4 Comparative Example 1 135.2 Comparative Example 2 136.3

[0141] As shown in Table 1, the biomedical alloy materials obtained in Examples 1 to 3 have the effect of promoting cell proliferation and good biocompatibility. Comparative Example 1 replaces Cu with Ta in step (1), and Comparative Example 2 omits polyacrylamide modification in step (1), and the biocompatibility is slightly poor, indicating that the specific combination of metals and hydrophilic modification are conducive to improving biocompatibility.

[0142] 2. Mechanical and piezoelectric properties

[0143] The biomedical alloy materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were tested for yield strength and elastic modulus using a universal mechanical testing machine, and for impact toughness and wear resistance according to GB / T 1817-2017. The results are shown in Table 2.

[0144] The wear resistance test method is as follows: the wear degree r is used to represent the wear resistance. The test method is to use water as the medium, place a 1cm×1cm×1cm sample on a JZ7502 grinding wheel wet wear tester, and use a TL80 R2A·B250 large-pore green silicon carbide grinding wheel. After grinding at a speed of 98r / min for 300 turns under a load of 40N, the wear amount per unit area is measured and calculated using the following formula: r=(M1-M2) / S, where M1 is the mass of the sample before grinding (g); M2 is the mass of the sample after grinding (g); S is the wear area of ​​the sample (cm 2 ).

[0145] Table 2. Mechanical properties and wear resistance results

[0146]

[0147] As shown in Table 2, the yield strength and elastic modulus of the biomedical alloy materials obtained in Examples 1 to 3 are close to the yield strength (133-193 MPa) and elastic modulus (3-20 GPa) of human cortical bone, and the impact toughness and wear resistance are good, meeting the requirements of orthopedic implant materials.

[0148] In comparative example 1, Ta is used to replace Cu in step (1); in comparative example 2, polyacrylamide modification is omitted in step (1); in comparative example 3, glycidyl-modified silk fibroin is replaced with silk fibroin in step (2), and polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) is omitted; in comparative example 4, no fiber form is prepared, and the strength and wear resistance of the product are deteriorated, indicating that the cross-linked structure formed by the modification treatment is beneficial to the improvement of mechanical properties, impact toughness, wear resistance and other indicators.

[0149] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0150] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a fiber-reinforced toughened biomedical alloy material, characterized in that: The specific steps are as follows: (1) firstly, Cu, Zr, Si and Ti with a purity of 99.9999% are mixed in a molar ratio of 100:8-10:20-30:20-30 and subjected to high-speed ball milling to obtain nano-amorphous powder, and then polyacrylamide is modified on the surface of the nano-amorphous powder to obtain modified nano-amorphous powder; (2) preparing a spinning solution by mixing glycidyl-modified silk fibroin with polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate), trifluoroethyl methacrylate, a fluorine-containing photoinitiator and deionized water under light-proof conditions, electrospinning the solution under ultraviolet light to obtain fibers, and cutting the fibers into short fibers of 1 to 2 mm; (3) finally, the modified nano-amorphous powder and the short fibers are subjected to cold pressing, vacuum sintering and pressure densification according to a mass ratio of 1:0.1 to 0.2 to obtain the biomedical alloy material; In step (2), the spinning solution is prepared as follows, in parts by weight: first, 1 to 2 parts of glycidyl-modified silk fibroin and 0.1 to 0.2 parts of polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) are added to 100 parts of deionized water, and stirred until completely dissolved. Then, 0.05 to 0.08 parts of trifluoroethyl methacrylate and 0.02 to 0.03 parts of a fluorine-containing photoinitiator are added under light-proof conditions, and stirred until completely dissolved, to obtain the spinning solution.

2. The preparation method according to claim 1, characterized in that: In step (1), the process conditions of high-speed ball milling are as follows: the mass ratio of the grinding balls to the large and small balls is 1:2, the diameters of the large and small balls are 8 mm and 5 mm respectively, the ball-to-material ratio is 1.05:1, argon gas protection is used during the ball milling process, the ball milling speed is 300 r / min, and the grinding time is 12 to 15 hours, wherein the preparation work before ball milling should be carried out in a vacuum glove box.

3. The preparation method according to claim 1, characterized in that: In step (1), the preparation method of the modified nano-amorphous powder is as follows, based on parts by weight: first, 1 part of nano-amorphous powder and 0.002-0.003 parts of initiator are added to 5-8 parts of 20-30% mass concentration of acrylamide aqueous solution, and ultrasonically oscillated at 400-500W for 30-40 minutes to obtain a premixed solution; then, ultraviolet light is irradiated to initiate a polymerization reaction of acrylamide to obtain the modified nano-amorphous powder.

4. The preparation method according to claim 1, characterized in that: In step (2), the process conditions of electrospinning are: spinning voltage 10-20 kV, the distance from the spinning nozzle to the receiver is 20-25 cm, the spinning nozzle diameter is 1.0 mm, and the flow rate is controlled at 1.5-2 mL / h.

5. The preparation method according to claim 1, characterized in that: In step (2), the glycidol-modified silk fibroin is prepared by the following method, based on parts by weight: first, 1 part of silk fibroin, 0.2-0.3 parts of glycidol and 0.1-0.2 parts of sodium chloride are added to 10-12 parts of deionized water, stirred until completely dissolved, stirred and reacted at 60-70° C. for 2-3 hours, naturally cooled to room temperature, and rinsed with deionized water for 2-4 days to remove unreacted substances, thereby obtaining the glycidol-modified silk fibroin.

6. The preparation method according to claim 1, characterized in that: In step (2), the polyacrylamide-modified poly(3-hydroxybutyrate-co-3-hydroxyvalerate) is prepared by the following method, based on parts by weight: first, 1 part of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) and 0.002-0.003 parts of initiator are added to 5-8 parts of 20-30% mass concentration acrylamide aqueous solution, and ultrasonically oscillated at 400-500W for 30-40 minutes to obtain a premixed solution; and then ultraviolet light is irradiated to initiate a polymerization reaction of acrylamide to obtain the obtained solution.

7. The preparation method according to claim 6, characterized in that: The initiator is benzophenone, tetraethyl Michler's ketone or 4-isopropylthioxanthone; and the ultraviolet light irradiation time is 2 to 3 hours.

8. The preparation method according to claim 1, characterized in that: The specific method of step (3) is as follows: the modified nano-amorphous powder and the short fibers are uniformly mixed and then transferred to a high-strength graphite mold for cold compaction, and then transferred to a vacuum hot pressing furnace for heating and degassing, vacuum sintering at 150-180°C and 60-90MPa for 50-80 minutes, naturally cooling to 80-90°C, and pressurizing and densifying at 50-60MPa for 4-6 hours to obtain the biomedical alloy material.

9. A fiber-reinforced and toughened biomedical alloy material obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • A titanium oxide-titanium carbide whisker toughened magnesium alloy biomedical material

    CN106119742B

  • Preparation method of fibroin / nano SiO2 blending membrane

    CN101579538A

  • Preparing method of medical material

    CN107881591A